PENGEMBANGAN ALAT PENGISI SELAI KOPI KE DALAM BOTOL UNTUK UMKM SEJAHTERA SENTOSA - Muladi, Muladi; Aripriharta, Aripriharta; Wibawa, Aji Prasetya; Handayani, Anik Nur; Suryani, Ani Wilujeng (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2021)
Coffee is one of the leading export commodities in Indonesia besides palm oil, cocoa and rubber. The quality of Indonesian coffee is among the best in the world, thus placing Indonesia in the top ten producers and exporters of the world. Coffee production continues to increase every year, accompanied by an increase in processed coffee-based products. Among the innovative creations of coffee products are UMKM Sejahtera Sentosa with their coffee jam products. This product received a good response and became the superior product of Malang Municipality. These MSMEs experienced difficulties in the production process when developing jam packaging in the form of sachets and bottles. The community service activity of the State University of Malang helped overcome this difficulty by developing a jam filling device for sachets and bottles. The filling device works semi-automatically with electronic control. The tools developed have been tested and can function according to the needs of industrial partners. UMKM owners and employees expressed their satisfaction with the tools developed and hope to work together again in the next service activity.